2019
DOI: 10.1108/mrjiam-05-2019-0921
|View full text |Cite
|
Sign up to set email alerts
|

Organizational learning, authentic leadership and individual-level resistance to change

Abstract: Purpose This paper aims to focus on academics in three private foreign universities located in Cairo (Egypt) to explore the effect of organizational learning on individual-level resistance to change with and without the mediation of authentic leadership. Design/methodology/approach A total of 960 academics were contacted and all of them received a set of questionnaires. After four follow ups, a total of 576 responses were collected with a response rate of 60.00 per cent. The author used the chi-square test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 114 publications
(120 reference statements)
0
18
0
2
Order By: Relevance
“…Even though organizations should use their ability to recognise and acquire new information, assimilate knowledge and then apply it to commercial ends (Cohen & Levinthal, 1990), the mechanism through which banks in this study recruit sources of training, the timing of the training sessions and the methods of selecting the participants (bankers) for those training opportunities come in disagreement with this theory and with what has been highlighted earlier by Mousa and Ayoubi (2019), who consider nepotism as a determinant factor in giving rewards and awards in the Egyptian public sector. This contradicts recommendations by Alas et al (2009), who urge transparent institutional procedures in addition to a kind of cultural equality for the effective functioning of organizational learning.…”
Section: Theoretical Implicationsmentioning
confidence: 76%
See 3 more Smart Citations
“…Even though organizations should use their ability to recognise and acquire new information, assimilate knowledge and then apply it to commercial ends (Cohen & Levinthal, 1990), the mechanism through which banks in this study recruit sources of training, the timing of the training sessions and the methods of selecting the participants (bankers) for those training opportunities come in disagreement with this theory and with what has been highlighted earlier by Mousa and Ayoubi (2019), who consider nepotism as a determinant factor in giving rewards and awards in the Egyptian public sector. This contradicts recommendations by Alas et al (2009), who urge transparent institutional procedures in addition to a kind of cultural equality for the effective functioning of organizational learning.…”
Section: Theoretical Implicationsmentioning
confidence: 76%
“…Siddiqui et al (2019) found that organizational learning plays a significant role between knowledge sharing and innovation capabilities in the banking sector in Pakistan. Mousa et al (2019) found that strategic leadership in public banking sector is the primary foundation for learning in organizations. Similarly, Thakur et al (2017) studied the presence of learning dimensions in public and private banks in India and found that managerial level does not affect the perception of employees regarding the bank as a learning organization, and that connection with external environment and strategic leadership are considered as the most important dimensions in the banking sector in India.…”
Section: Practices Of Organizational Learning Through Training In Pub...mentioning
confidence: 99%
See 2 more Smart Citations
“…Diante dos estudos apresentados, e com as crescentes demandas por ética e integridade, a necessidade de um estilo de liderança mais adaptável e baseado em valor, foi solicitada como resposta. A liderança autêntica tem recebido considerável atenção tanto por muitos estudiosos da gestão geral, quanto do comportamento organizacional, em que ambos investigaram a sua relação com o envolvimento com o trabalho e exploraram sua associação com o comportamento de cidadania organizacional, elaboraram sobre seu impacto no desempenho organizacional e, finalmente, que demonstraram seu efeito sobre as intenções de rotatividade de funcionários (Chaudhary & Panda, 2018;Mousa, Massoud & Ayoubi, 2020).…”
Section: Itensunclassified